O1.6. TELOMERE LENGTH IS ASSOCIATED WITH CHILDHOOD TRAUMA IN PATIENTS WITH SEVERE MENTAL DISORDERS - Aas, Monica (Schizophr Bull, 2019)
BACKGROUND: Reduced telomere length (TL) and structural brain abnormalities have been reported in patients with schizophrenia (SZ) and bipolar disorder (BD). Childhood traumatic events are more frequent in SZ and BD than in healthy individuals (HC), and based on recent findings in healthy individuals could represent one important factor for TL and brain aberrations in patients. METHODS: The study comprised 1024 individuals (SZ [n=373]; BD [n=249], and HC [n=402]). TL was measured by quantitative polymerase chain reaction (qPCR), and childhood trauma was assessed using the Childhood Trauma Questionnaire (CTQ). Diagnosis was obtained by the Structured Clinical Interview (SCID) for the Diagnostic and Statistical Manual of Mental Disorders-IV (DSM-IV). FreeSurfer was used to obtain regional and global brain volumes from T1- weighted magnetic resonance imaging (MRI) brain scans. All analyses were adjusted for current age and sex. RESULTS: Patients had on average shorter TL (F=7.87, p=0.005, Cohen’s d=0.17) and reported more childhood trauma experiences than HC (χ2=148.9, p˂0.001). Patients with a history of childhood sexual, physical or emotional abuse had shorter TL relative to HC and to patients without a history of childhood abuse (F=6.24, p=0.01, Cohen’s d=0.16). After adjusting for childhood abuse, no difference in TL was observed between patients and HC (p=0.27). Our analyses revealed no significant associations between TL and clinical characteristics or brain morphometry. DISCUSSION: We demonstrate shorter TL in SZ and BD compared to HC and found that TL is negatively associated with childhood trauma experiences. Further studies are needed to identify the biological mechanisms of this relationship.